Peningkatan Pemahaman Guru-Guru SMK melalui Pelatihan Akuntansi Pemerintah Guna Menyiapkan SDM Instansi Pemerintah - Anggraini, Ratna; Hasanah, Nuramalia; Fauzi, Ahmad; Utaminingtyas, Tri Hesti (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2018)
The development of the implementation of financial accountability in government institutions, demands an increase in the number of human resources as executors of activities. Vocational secondary schools are government institutions that produce human resources that are ready to use are required to help fulfill these resources. Correspondingly, the government established a government accounting curriculum in vocational high schools in 2018. However, the constraints faced by vocational teachers in the accounting field, many still do not understand policy changes in government accounting, even though they are required to be able to teach government accounting subjects in the class. Responding to this, Jakarta State University as an educational institution is obliged to carry out community service to conduct training activities for vocational teachers in East Jakarta in an effort to increase the capacity to prepare government institutions for the government.